171 The right ventricle of the endurance athlete: the relationship between morphology and deformation. (9th June 2011) - Oxborough, D; Shave, R; Whyte, G; Birch, K; Artis, N; George, K; Sharma, S
Abstract : Introduction: It is well established that endurance exercise results in cardiac adaptation including eccentric hypertrophy of the left ventricle which can complicate the differential diagnosis of the athletic heart from some cardiac pathologies that may pre-dispose to sudden cardiac death. The impact of physiological conditioning on RV structure and function, and a similar diagnostic challenge with arrhythmogenic right ventricular cardiomyopathy (ARVC), has received less attention. A recent guideline paper from the American Society of Echocardiography (ASE) has provided a range for normal RV dimensions and functional deformation. These guidelines suggest the RV inflow (RVI) should be <42 mm while the proximal outflow tract (RVOT) <35 mm. A recent paper also suggested that an RVOT dimension >36 mm or 21 mm/m 2 is a major criterion for the diagnosis of ARVC and furthermore longitudinal RV deformation has been shown to be impaired in these patients. In view of this, the aims of this study are twofold: To provide a range of absolute values for RV dimensions in 102 endurance athletes as well as providing a range of data indexed for body surface area (BSA). To provide normal athlete data for indices of RV strain (ɛ) and strain rate (SR). Methods and Results: One hundred and two (102) endurance athletes (86 males and 16 females) with a broad age range (mean ± SD age (range)=36 ± 11 (21–71) years) volunteered and were consecutively enrolled in the study. All subjects were either endurance runners or cyclists and were scanned at peak condition. Echocardiography provided measurements of RVI, RV length, RVOT and RV diastolic area (RVDarea). A 2D strain technique was utilised to provide indices of RVɛ and systolic and diastolic SR. The values for RVI ranged from 30 to 55 mm with 57% of the population having values greater than the normal range. Proximal RVOT ranged from 26 to 49 mm with 40% of the population above the normal range. 28% of the population had RVOT values greater than the proposed "major criteria" for ARVC. RV length ranged from 70 to 110 mm and RVDarea from 13 to 38 cm 2 with values falling above ASE cut-offs in 69% and 59% of the population, respectively. When indexed (ratio scaling) for BSA proximal RVOT ranged from 13 to 25 mm/m 2 with 6% of the population meeting the major criteria for ARVC. Peak RVɛ ranged from −18 to −41% and peak RV SRS′ from −0.75 to −2.65 l/s, consistent with normal ranges proposed by the ASE. RV diastolic deformation indices displayed marked individual variability with a dominant SRE′ (mean ± SD=2.0±0.61 l/s) and smaller SRA′ (1.25±0.56 l/s). Conclusion: RV dimensions in endurance athletes are higher than those proposed as "normal" and likewise may be consistent with the criteria for ARVC. Despite this enlargement, RV function in endurance athletes is preserved and therefore the role of RV strain imaging may provide additional diagnostic value in differentiating physiological from pathological adaptation.